Exploring cost and utilization outcomes of Huntsman at Home: Which patients benefit most from a novel oncology hospital at home program?. Issue 28 (1st October 2022) - ONeil, Brock; Coombs, Lorinda A; Haaland, Ben; Ying, Jian; McPherson, Jordan P.; Kirchhoff, Anne C.; Ulrich, Cornelia; Huber, Jared S; Beck, Anna Catherine; Mooney, Kathi
Abstract : 15 Background: We previously demonstrated that Huntsman at Home (HH), a novel oncology hospital at home program, was associated with reduced healthcare utilization and costs. HH was also linked to shorter hospital stays and fewer emergency room (ER) visits. In this study, we sought to understand the impact of HH in specific patient subgroups. Methods: We compared outcomes among 169 patients consecutively admitted to HH against 198 usual care patients. Five dichotomous subgroups were created based upon patient a) sex b) age c) area level median income d) Charlson Comorbidity Index (CCI), and e) current use of systemic therapy (ST). Outcomes included 30-day costs, unplanned hospitalizations (UH), length of hospital stays, and ER visits. HH and usual care were compared via inverse propensity weighted regression models. Treatment propensities were estimated via random forests based on age, race, stage, cancer site, presence of metastases, CCI, and area level median income.Results: The between group difference favoring HH achieved statistical significance (p < 0.05) for at least two out of the four outcomes in each subgroup except for patients with higher comorbid illnesses. While HH participants did not always experience statistically better outcomes than usual care, none of the outcomes examined favored usual care for any subgroup. Sex. Female and male HH patients experienced fewer UH and lower costs than usual care. Male HH patients also had shorter hospital stays and fewer ED visits. Age. When stratifying age at 65 years, older HH patients experienced fewer days in the hospital and fewer UH. Younger HH patients had lower costs, and fewer UH and ED visits. Area level Income. All outcomes were better for high and low income HH patients compared to usual care except for ED visits among those with low income. CCI. Among those with a low CCI score, all four outcomes were better among HH patients. In contrast, differences between groups with higher comorbid illness did not achieve statistical significance for any outcome. Systemic Therapy. HH participants on ST experienced shorter hospital stays and fewer UH compared to usual care. Among those not on ST, HH patients experienced lower costs, and fewer UH and ED admissions. Conclusions: In this exploratory analysis, we found that the utilization and cost benefit associated with HH was robust, favoring better outcomes in each subgroup including lower 30-day costs, shorter hospital length of stay and fewer unplanned hospitalizations or ER visits. While medically complex patients may not receive similar benefit from HH as other subgroups, no outcomes favored patients managed by usual care. Taken together, this suggests that health care utilization and cost reductions associated with HH occur across multiple subgroups, but patients with high comorbidity may require additional intervention to realize lower utilization and costs.